Heat tolerance in common bean derived from interspecific crosses - Polanía Perdomo, José A.; Chaves, N.; Lobaton, Juan David; Cajiao V., César Hernando; Rao, Idupulapati M.; Raatz, Bodo; Beebe, Stephen E. (International Center for Tropical Agriculture, 2017)
Many Countries could experience unprecedented heat stress because of global climate change (Battisti and Naylor,2009). Heat sensitivity in common bean is a major limiting factor that can reduce yield, quality, and lead to restricted geographic adaptation (Beebeetal.,2011). Interspecific lines developed with crosses between P.vulgaris and P. acutifolius were evaluated for their tolerance to heat stress. Results from field and greenhouse evaluation confirmed that Phaseolus acutifolius is an important and useful genetic resource for improving heat tolerance in common bean. Results from genomic analysis indicated the introgression of P. acutifolious genes into interspecific INB line that was used as apparent for developing heat tolerant SEF lines.